2009
DOI: 10.1563/aaid-joi-d-09-00022.1
|View full text |Cite
|
Sign up to set email alerts
|

Platform Switching and Bone Platform Switching

Abstract: Bone platform switching involves an inward bone ring in the coronal part of the implant that is in continuity with the alveolar bone crest. Bone platform switching is obtained by using a dental fixture with a reverse conical neck. A retrospective study was performed to evaluate the effectiveness of conventional vs reverse conical neck implants. In the period between May 2004 and November 2007, 86 patients (55 females and 31 males; median age, 53 years) were operated and 234 implants were inserted: 40 and 194 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 8 publications
(9 reference statements)
0
9
0
1
Order By: Relevance
“…Researches have challenged several aspects of this specific protocol, and their investigations found the relative importance of helix design on osseointegration. Therefore, the identification of guidelines for the long-term success (i.e., total implants still in place at the end of the follow-up, good clinical, radiologic, and aesthetic outcome) has been to achieve good clinical outcome (17)(18)(19)(20). Many variables may influence the clinical outcome of SDI: surgery protocol, bone quality and quantity, helix design, and occlusion (21)(22)(23)(24)(25).…”
Section: A New Spiral Dental Implantmentioning
confidence: 99%
“…Researches have challenged several aspects of this specific protocol, and their investigations found the relative importance of helix design on osseointegration. Therefore, the identification of guidelines for the long-term success (i.e., total implants still in place at the end of the follow-up, good clinical, radiologic, and aesthetic outcome) has been to achieve good clinical outcome (17)(18)(19)(20). Many variables may influence the clinical outcome of SDI: surgery protocol, bone quality and quantity, helix design, and occlusion (21)(22)(23)(24)(25).…”
Section: A New Spiral Dental Implantmentioning
confidence: 99%
“…This type of implant produces increased residual crestal bone volume and carries several advantages like reduced stress and repositioning of gingival papillae. 2 Ericsson et al indicated that the bone is always encircled by approximately 1 mm of healthy connective tissue, so it can be assumed that crestal bone remodeling takes place to create space between the bone and inflammatory cell tissue (ICT) to establish a biologic seal. PLS refers to the use of a smaller diameter abutment on a larger diameter implant collar.…”
Section: Definitionmentioning
confidence: 99%
“…This type of connection moves the perimeter of implant abutment junction (IAJ) to the center of implant axis. It is possible that moving the (IAJ) inward brings out bacteria more internally and, therefore, away from the bone crest; this would explain the limitation in bone resorption 9,10 . According to Carinci et al 11 platform switching can be achieved by using abutments with a diameter smaller than the implant neck or body width, by increasing the implant neck diameter with respect to the implant body width, using platform-switched implants and conical emergence abutments and finally using implants with a reverse conical neck referred to as Bone Platform Switching. This embraces an inward bone ring in the coronal part of the implant that is in continuity with the alveolar bone crest.…”
Section: Introductionmentioning
confidence: 99%